Indigenous research methods and African women’s theology: A theo-analytical engagement - J. Gathogo (Acta Theologica, 2025)
This article seeks to address the following question: To what extent can we draw a parallel between the methodology of African women’s theology and that of African indigenous research? It sets out on the premise that indigenous methodologies strive towards research authenticity, from an insider perspective, as opposed to an outsider’s overview. Understanding the concept of relationality in the indigenous methods is critically important as we comparatively engage African women’s theology. Does the latter embrace an all-inclusive approach that encompasses axiology (aesthetics and ethics), epistemology (knowledge and truth), political philosophy (the state and government), logic (argumentation and reason), and metaphysics (reality and being), as in the former? In vouching for a cosmological interconnectedness, women theologians have approached their discourses from a broad spectrum that seeks to preserve and nurture a two-winged society of men and women. In using a theo-analytical engagement, this article reviews relevant literature, in order to understand its concern.